Ekstrak Buah Etlingera elatior dan Penyembuhan Ulkus Diabetik: Tinjauan Literatur terhadap Bukti Tidak Langsung dan Kesenjangan Penelitian - Chrismas Gideon Bangun; Gusbakti Rusip; Maya Sari Mutia; Yolanda Eliza Putri Lubis (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Diabetic ulcers are major complications of diabetes mellitus and remain a significant clinical challenge due to impaired wound healing, persistent inflammation, oxidative stress, and increased susceptibility to infection. Natural products with antioxidant, anti-inflammatory, and antimicrobial properties have been increasingly investigated as complementary therapies for diabetic wound management. Etlingera elatior (torch ginger) is a tropical medicinal plant containing bioactive compounds with promising pharmacological activities. However, its potential role in diabetic ulcer treatment has not been systematically evaluated. This study aimed to assess available evidence regarding the potential effects of E. elatior fruit extract on diabetic ulcers in animal models through a literature review with a systematic search approach. Literature searches were conducted in Google Scholar and Scopus databases, followed by screening using predefined inclusion criteria related to animal studies, diabetic ulcer models, and E. elatior fruit extract intervention. The selection process followed the PRISMA framework. No study directly tested E. elatior fruit extract on diabetic ulcers in animal models. However, indirect evidence showed strong biological plausibility. Ethanol extract of E. elatior fruit demonstrated anti-hyperglycemic effects in diabetic rodents, with 400 mg/kgBW identified as the most effective dose for reducing plasma glucose and protecting pancreatic β-cells. Other studies reported significant reduction of hsCRP (p < 0.05), improvement in renal function, and antioxidant and antimicrobial activities. Major compounds included quercetin, vanillic acid, p-coumaric acid, and other phenolic and flavonoid compounds. These findings suggest potential therapeutic relevance, although direct in vivo diabetic wound studies are still required.